Single iterated fractal inspired UWB antenna with reconfigurable notch bands for compact electronics - Musa Hussain; Tanvir Islam; Mohammed S. Alzaidi; Dalia H. Elkamchouchi; Fahad N. Alsunaydih; Fahd Alsaleem; Khaled Alhassoon (Heliyon, 2023)
A simple, compact, and low-profile antenna operating over ultrawideband with high gain is presented in this manuscript. The antenna has dimensions of W × L = 19 mm × 21 mm and is placed on the rear side of the FR-4 substrate material. The antenna contains simple geometry, inspired from a circular fractals, which consists of a circular patch with a CPW feedline. The circular patch is loaded with two fractals patches at both top end of the substrate and the rectangular stub is loaded at the lower side, to improve the antenna's bandwidth. The constructed antenna offers a wide band of 3–13.5 GHz. The antenna geometry also contains three semicircular slots, which are etched to generate the notch bands. Each slot is etched step by step, giving notch bands at 3.9 GHz, 5.2 GHz, and 8.1 GHz. In the final stage, two diodes are added to attain reconfiguration. The antenna offers moderate gain and high radiation efficiency. The hardware model of antenna is engineered to verify the simulated results. Moreover, the antenna is compared with other works in literature. The outcomes of the proposed antenna and comparison with the literature work make the suggested work the best candidate for future UWB portable devices.